Accounting standards and value relevance of accounting information: a comparative analysis between Islamic, conventional and hybrid banks. Issue 1 (8th December 2020) - Agbodjo, Serge; Toumi, Kaouther; Hussainey, Khaled
Abstract : Purpose: The purpose of this study is to investigate the value relevance of accounting information for Islamic, conventional and hybrid banks. It also investigates the moderation impact of IFRS adoption and AAOIFI mandatory adoption on value relevance of accounting information. Design/methodology/approach: Using value relevance models, The authors run panel data regressions on 47 Islamic banks, 112 conventional banks and 42 hybrid banks (conventional banks with Islamic windows). The study covers listed banks from 14 countries over the period 2010–2018. Findings: paper offers three empirical evidences. First, the authors find that value relevance of accounting information is higher for Islamic banks, compared to conventional banks. Second, the authors find that IFRS framework strengthens the relevance of accounting information in Islamic banks, but the authors did not find the same for hybrid banks. Third, the authors find that the mandatory adoption of AAOIFI accounting standards has a moderation effect on value relevance of accounting information for both Islamic banks and hybrid banks. The robustness analysis shows that there is a significant contribution of compliance with Islamic Finance rules in IBs and HBs, which substantially reduces managers' opportunistic behavior to manage accounting information. Research limitations/implications: One limit of this research is the reduced number of sampled listed IBs since the authors deleted countries that do not have both listed Islamic and conventional banks. Practical implications: The study is useful for investors that consider the Islamic ethical practices to make their investment decisions as well as for the standards-setting bodies that focus on establishing accounting standards for the Islamic banking industry. Originality/value: The authors contribute to the value relevance literature by providing novel evidence on the value relevance in fully-fledged Islamic, fully-fledged conventional and hybrid Banks. The authors also provide new evidence on the moderating role of International Financial Reporting Standards (IFRS) and Auditing Organization for Islamic Financial Institutions standard (AAOIFI) for the value relevance of accounting information.